A prospective, randomised study of a novel transforming methacrylate dressing compared with a silver‐containing sodium carboxymethylcellulose dressing on partial‐thickness skin graft donor sites in burn patients. Issue 3 (6th August 2013) - Assadian, Ojan; Arnoldo, Brett; Purdue, Gary; Burris, Agnes; Skrinjar, Edda; Duschek, Nikolaus; Leaper, David J
Abstract This prospective, randomised study compares a new transforming methacrylate dressing (TMD) with a silver‐containing carboxymethylcellulose dressing (CMC‐Ag) after application to split‐thickness skin graft (STSG) donor sites. This was an unblinded, non‐inferiority, between‐patient, comparison study that involved patients admitted to a single‐centre burn unit who required two skin graft donor sites. Each patient's donor sites were covered immediately after surgery: one donor site with TMD and the other with CMC‐Ag. The donor sites were evaluated until healing or until 24 days post‐application, whichever came first. Study endpoints were time to healing, daily pain scores, number of dressing changes, patient comfort and physicians' and patients' willingness to use the dressings in the future. Nineteen patients had both the dressings applied. No statistically significant difference was noted in time to healing between the two dressings (14·2 days using TMD compared with 13·2 days using CMC‐Ag). When pain scores were compared, TMD resulted in statistically significantly less pain at three different time periods (2–5 days, 6–10 days and 11–15 days; P < 0·001 at all time periods). Patients also reported greater comfort with TMD (P < 0·001). Users rated TMD as being less easy to use because of the time and technique required for application. Reductions in pain and increased patient comfort with the use of the TMD dressing, compared with CMC‐Ag, were seen as clinical benefits as these are the major issues in donor site management.